Secondary structure analysis of peptides with relevance to iron–sulfur cluster nesting1. Issue 2 (12th December 2018) - Hanscam, Rebecca; Shepard, Eric M.; Broderick, Joan B.; Copié, Valérie; Szilagyi, Robert K.
Abstract : Peptides coordinated to iron–sulfur clusters, referred to as maquettes, represent a synthetic strategy for constructing biomimetic models of iron–sulfur metalloproteins. These maquettes have been successfully employed as building blocks of engineered heme‐containing proteins with electron‐transfer functionality; however, they have yet to be explored in reactivity studies. The concept of iron–sulfur nesting in peptides is a leading hypothesis in Origins‐of‐Life research as a plausible path to bridge the discontinuity between prebiotic chemical transformations and extant enzyme catalysis. Based on past biomimetic and biochemical research, we put forward a mechanism of maquette reconstitution that guides our development of computational tools and methodologies. In this study, we examined a key feature of the first stage of maquette formation, which is the secondary structure of aqueous peptide models using molecular dynamics simulations based on the AMBER99SB empirical force field. We compared and contrasted S…S distances, [2Fe‐2S] and [4Fe‐4S] nests, and peptide conformations via Ramachandran plots for dissolved Cys and Gly amino acids, the CGGCGGC 7‐mer, and the GGCGGGCGGCGGW 16‐mer peptide. Analytical tools were developed for following the evolution of secondary structural features related to [Fe‐S] cluster nesting along 100 ns trajectories. Simulations demonstrated the omnipresence of peptide nests for preformed [2Fe‐2S] clusters; however, [4Fe‐4S] cluster nests were observed only for the 16‐mer peptide with lifetimes of a few nanoseconds. The origin of the [4Fe‐4S] nest and its stability was linked to a "kinked‐ribbon" peptide conformation. Our computational approach lays the foundation for transitioning into subsequent stages of maquette reconstitution, those being the formation of iron ion/iron–sulfur coordinated peptides. © 2018 Wiley Periodicals, Inc. Abstract : A secondary structure analysis toolkit is described for characterizing S(Cys)…S(Cys) distances, peptide conformations accommodating [2Fe‐2S] rhombs or [4Fe‐4S] cubanes, and their lifetime in the context of iron–sulfur peptides maquettes. Using empirical force field‐based molecular dynamics trajectories of free amino acids, short 7‐mer, and long 16‐mer peptides in approximately 6 nm sized water bath, the authors discovered the omnipresence of [2Fe‐2S] cluster nests and some specific peptide secondary structures that are favorable for [4Fe‐4S] peptide maquette formation.